Solid waste: impact on economic - Ramlee, Nur Atiqah Zakiyyah; Hussin, Siti Nor Adawiah; Abdullah @ Abd Aziz, Azilawati; Zainan, Nurul Izzah Noor; Awang @ Abd Rahman, Nurul Hidayah (Universiti Teknologi MARA, Kelantan, 2018)
As the population in Malaysia is increasing, solid waste management is crucial to ensure future sustainability. Solid waste is useless and unwanted products in the solid form which derived from discard activities from society. Its comprehends with activities of control, generation, storage, collection, transfer and transportation, processing and disposal of solid waste consistent with the best practices of public health, economics and finance, engineering, administration, legal and environmental considerations. It became issues towards national economy as the cost of disposing of solid waste increases from time to time with potential damages towards next generation living. In addition, the country may benefit from solid waste management through recycling which has been well-practiced by many countries. Solid waste has been acknowledged as an income generator to the society, in line with rapid growth in population, urbanization and industrialization in Malaysia. This conceptual study will be carried out in the East Coast Region of Malaysia by using relevant data and relevant data analysis methods. The discussion of this paper will contribute to the solid waste industry growth in East Cost of Malaysia and also contributes to the academic bodies to further enlighten on solid waste impact towards economy.